"In such a dark period, the only light": Patients' motivations and strategies to seek care from an online health community during the COVID-19 pandemic - Alberto Ardissone (Elsevier, 2024)
This paper presents the findings of a qualitative study conducted in Italy about a peculiar online health community named #TERAPIADOMICILIARECOVID19 (#TDC19), which, since April 2020, has assisted people with COVID-19 with early-at-home therapy delivered by volunteer doctors, free of charge for patients. The aim of the paper was to analyse patients' motivations and strategies when negotiating risk in the context of this choice. Findings showed that patients' choices were the outcome of a process that forms an entangled ecology of care involving several dimensions, crossing micro, meso and macro levels: a) the process of knowledge-building by assessing mass-media, ascertaining the best protocol and recalling previous experiences with similar diseases; b) the experience of feeling abandoned by general practitioners (GPs) and healthcare institutions; c) the positive encounter with #TDC19's posts of gratitude written by people who were cured by #TDC19 doctors. In the end, patients' choice was not a leap of faith; they negotiated and balanced out the perceived risks associated with COVID-19 and with the possible available choices (GPs, do-it-yourself, #TDC19-doctors) based on a strategy that chiefly encompassed a blend of rational and in-between logics.